2009
DOI: 10.1016/j.autneu.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Direct and consensual murine pupillary reflex metrics: Establishing normative values

Abstract: Pupillometry is a non-invasive technique, based on well-established neurophysiologic principles, that can be utilized to objectively characterize pathophysiologic demyelinating and neurodegenerative changes involving the pupillary reflex pathway. In animal models of human disorders, pupillometry derived reflex metrics could potentially be used to longitudinally monitor disease activity and responses to pharmacotherapies. These investigations would have important implications for translational initiatives focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…S5) and provided evidence of calcium homeostasis that is essential for photoreceptor maintenance. We used the pupil light response (PLR) (19), which has been validated in similar studies (3,(20)(21)(22), as a functional test that would prove not only the existence of light-sensing OS but also that efferent connections existed to central targets. We aimed to test for an improvement above the zero baseline in these mice that were structurally and functionally devoid of rods at the time of intervention and therefore measured the PLR before and after treatment to compare outcomes pairwise in the same animal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5) and provided evidence of calcium homeostasis that is essential for photoreceptor maintenance. We used the pupil light response (PLR) (19), which has been validated in similar studies (3,(20)(21)(22), as a functional test that would prove not only the existence of light-sensing OS but also that efferent connections existed to central targets. We aimed to test for an improvement above the zero baseline in these mice that were structurally and functionally devoid of rods at the time of intervention and therefore measured the PLR before and after treatment to compare outcomes pairwise in the same animal.…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to test for an improvement above the zero baseline in these mice that were structurally and functionally devoid of rods at the time of intervention and therefore measured the PLR before and after treatment to compare outcomes pairwise in the same animal. To avoid influences such as transplantation-related inflammation, we stimulated the transplanted eye and measured the consensual PLR (19) (Fig. 4A) in the unoperated eye after precursor cell transplantation (n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…Pupillary responses have been used as important measures of optic nerve function in optic neuritis and MS patients (Ellis, 1979; Beck et al, 1992; Surakka et al, 2008). Pupillometry has been used recently to characterize normal murine pupillary light responses and the role of melanopsin-containing RGCs (Zhu et al, 2007; Hussain et al, 2009). A potential role for pupillometry in monitoring optic nerve function in EAE mice was suggested (Hussain et al, 2009), but has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Pupillometry has been used recently to characterize normal murine pupillary light responses and the role of melanopsin-containing RGCs (Zhu et al, 2007; Hussain et al, 2009). A potential role for pupillometry in monitoring optic nerve function in EAE mice was suggested (Hussain et al, 2009), but has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2) to measure the murine pupillary light reflex (Mure et al, 2007;Hussain et al, 2009). Recently similar LED-based chromatic pupillometry was employed by Herbst et al (2011) to study the human pupillary light reflex (PLR).…”
Section: Mouse Pupillometrymentioning
confidence: 99%